EFFECT OF GCG AND FINANCIAL PERFORMANCE ON THE QUALITY OF INTERNET FINANCIAL REPORTING - wahyuni, putri dwi; Mahliza, Febrina (Universitas Pamulang, 2019)
This study aims to analyze and measure the effect of the mechanism of Good Corporate Governance and Financial Performance on the quality of Internet Financial Reporting. This research was conducted in the manufacturing sector on the IDX during the 2015-2016 period. Based on the method of sample selection, the sample was obtained at the end of a study of 140 data with 70 issuers being 125 data from the manufacturing sector on the IDX. The analytical method used is multiple regression analysis. The t-test statistic was carried out before multiple regression equation analysis, in the first stage the classical assumption was tested which consisted of normality, multicollinearity, heteroscedasticity, and autocorrelation. Based on the results of the analysis, it is known that institutional ownership, the proportion of independent commissioners, frequency of meeting of commissioners, return on assets and leverage have no effect on Internet Financial Reporting. The coefficient of determination that sees the influence of the independent variable used in the research model of the dependent variable is 9.30%, while the rest (90.70%) is explained by other variables